Stirring System Design for Automatic Coffee Maker Using OMRON PLC and PID Control - Ashadi Setiawan; Alfian Ma'arif (International Journal of Robotics and Control Systems, 2021)
The implementation of the use of PLC in this study was designed for a small scale in the process of stirring coffee drinks at a speed of 600 RPM. To get a stable speed so that the water does not overflow, a control system is needed. To get optimal results, a system design that can control the stirring speed is arranged automatically using a Programmable Logic Controller (PLC). This system is designed using a rotary encoder sensor C38S6G5-600B-G24N as a speed reader obtained from the movement of the motor, DC Motor JGA25-370 12V as an actuator or stirrer. PLC OMRON CP1E-NA20DR-A is used as a motor speed control device using the Proportional Integral Derivative (PID) algorithm to control the system according to the setpoint entered. The motor speed control system with the PID algorithm shows a system response that works well according to the researchers' expectations. The response of the system obtained is fast enough to achieve a stable speed with a small overshoot value. Thus this system was successfully designed to control the stirring process of coffee drinks automatically and produce stable stirring by giving a set point of 600 RPM at the parameter constant Proportional band is 720%; Integral time is 1.6s; and Derivative time is 0.2s with a rise time value is 1.3s; settling time is 11s; overshoot is 1.1%; and steady-state error is 0.5%.